Frequency of Genital Tuberculosis in Patients Undergoing Diagnostic Laparoscopy for Infertility - Niaz, Hina; Khan, Asaf Alam (Journal of Gandhara Medical and Dental Science, 2022)
OBJECTIVES: To determine the frequency of genital tuberculosis in patients undergoing diagnostic laparoscopy for infertility. METHODOLOGY: It is a descriptive (cross-sectional) prospective study. The study was performed within the duration of six months i.e., February 12th, 2020 to August 12th, 2020 at the Department of Obstetrics and Gynecology, Khyber Teaching Hospital, Peshawar. A total of 196 patients were observed by using 47.1% proportion of genital tuberculosis in infertility, 95% confidence interval with margin of error 7%, using software of WHO for sample size calculation. Further, sample collection was performed using non-probability (consecutive) sampling techniques. RESULTS: The mean age of the patients in our study was 30 years (SD+3.92). Fifty seven percent of cases were having primary infertility and 43% of patients were having secondary infertility. The incidence of genital tuberculosis undergoing infertility was 45%. CONCLUSION: Our study concludes that the incidence of genital TB in infertility in our setup was 45%.